Asymmetric B cell division in the germinal center reaction - Barnett, Burton E. (2011)
Lifelong antibody responses to vaccination require reorganization of lymphoid tissue and dynamic inter-cellular communication called the germinal center reaction. B lymphocytes undergo cellular polarization during antigen stimulation, acquisition, and presentation, which are critical steps for initiating humoral immunity. Here we show that germinal center B lymphocytes asymmetrically segregate the transcriptional regulator Bcl6, the receptor for interleukin-21, and the ancestral polarity protein atypical PKC to one side of the plane of division, generating unequal inheritance of fate-altering molecules by daughter cells. Germinal center B lymphocytes from mice with a defect in leukocyte adhesion fail to divide asymmetrically. These results suggest that motile cells lacking constitutive attachment can receive provisional polarity cues from the micro-environment to generate daughter cell diversity and self-renewal.